Monetary policy frameworks in Asia: Experience, lessons, and issues - Peter J. Morgan (Asian Development Bank Institute (ADBI), 2013)
This paper analyzes the evolution of East Asian monetary policy frameworks over the past two decades, chiefly in response to shocks from the Asian financial crisis of 1997 - 1998 and the global financial crisis (GFC) of 2007 - 2009. The Asian financial crisis showed the importance of exchange rate flexibility and credible policy frameworks, leading to increased central bank independence, greater focus on inflation policy and more flexible exchange rates. A key lesson of the GFC was the importance of containing systemic financial risk and the need for a "macroprudential" approach to surveillance and regulation that can identify system-wide risks and take appropriate actions to maintain financial stability. Emerging economies face particular challenges because of their underdeveloped financial systems and vulnerability to volatile international capital flows, especially "sudden stops" or reversals of capital inflows. The paper reviews the history of East Asian monetary policy frameworks since 1990; describes current monetary policy frameworks, including issue of price versus financial stability for a central bank and the policies a central bank can use to manage financial stability; the monetary policy transmission mechanism based on financial linkages and financial deepening; assesses policy outcomes including inflation targeting and responses to the "Impossible Trinity"; and makes overall conclusions. The paper finds that East Asian central banks have generally managed inflation and growth well over the past decade, but the difficulties faced by central banks of advanced countries in the aftermath of the GFC suggests that not all problems have been solved yet.
Keywords: E52; E58; F31; F32; G18; 330; monetary policy; macroprudential policy; inflation targeting; financial stability; currency regime; capital flows; emerging economies; Geldpolitik; Geldpolitisches Ziel; Finanzkrise; Ostasien